(untitled) (Jurnal Simki Economic, 2025)
This study aims to analyze the effect of human resource quality and professionalism on employee performance. With a quantitative approach, data was obtained through distributing questionnaires to all employees totaling 31 people as respondents, who also became the population and sample of this study, because it used a census technique where all members of the population were sampled. The data analysis method used is multiple linear regression analysis. The results of the analysis show that both the quality of human resources and professionalism have a significant influence on employee performance, both partially and simultaneously. Human resource quality includes aspects of skills, knowledge, and work attitudes that affect productivity levels, while professionalism includes ethics, responsibility, and efficiency in carrying out tasks. This research emphasizes the importance of developing human resource quality and professionalism as strategic steps to optimize employee performance in an organization.